Oxytocin-induced antinociception in the spinal cord is mediated by a subpopulation of glutamatergic neurons in lamina I-II which amplify GABAergic inhibition - Schlichter Rémy; Freund-Mercier Marie; Vergnano Angela; Uhl-Bronner Sandra; Veinante Pierre; Breton Jean-Didier; Poisbeau Pierrick (Molecular Pain, 2008)
Abstract Background Recent evidence suggests that oxytocin (OT), secreted in the superficial spinal cord dorsal horn by descending axons of paraventricular hypothalamic nucleus (PVN) neurons, produces antinociception and analgesia. The spinal mechanism of OT is, however, still unclear and requires further investigation. We have used patch clamp recording of lamina II neurons in spinal cord slices and immunocytochemistry in order to identify PVN-activated neurons in the superficial layers of the spinal cord and attempted to determine how this neuronal population may lead to OT-mediated antinociception. Results We show that OT released during PVN stimulation specifically activates a subpopulation of lamina II glutamatergic interneurons which are localized in the most superficial layers of the dorsal horn of the spinal cord (lamina I-II). This OT-specific stimulation of glutamatergic neurons allows the recruitment of all GABAergic interneurons in lamina II which produces a generalized elevation of local inhibition, a phenomenon which might explain the reduction of incoming Aδ and C primary afferent-mediated sensory messages. Conclusion Our results obtained in lamina II of the spinal cord provide the first clear evidence of a specific local neuronal network that is activated by OT release to induce antinociception. This OT-specific pathway might represent a novel and interesting therapeutic target for the management of neuropathic and inflammatory pain.